O processo eleitoral e a reprodução de grupos políticos no Maranhão: embates recentes - Almeida, Alderico José Santos (2010)
Through this study, we propose to describe the political and electoral process in a poor state such as Maranhão, highlighting its main political forces and understand how they work, are reproduced and legitimated. However, the core of our research is to examine how the process of modernization and the actual progress of capitalist relations contributed to the evolution of the Colonels to sophisticated forms of political patronage, or the conversion of the vote in a bargaining tool, in which the transaction state is used, most often, as a middleman. Another goal of our work is to understand, too, why do Maranhão unable to develop economically, despite having potential conditions for growth. That is why we propose to also demonstrate the two faces of Maranhão, the first modern, in which each part of "big projects" that promise great results for the state's economy and the second of the delay, the extreme poverty of its population, as the social indicators, which we believe to be the locus for the persistence of political and electoral practices and the reproduction of oligarchic groups. For this work we made use of desk research, consultation with professional literature and field work, to characterize, mainly clientelist practices. We have reached a different result than found in most of the studies on practical electoral politics in the North and Northeast, which deny the exercise of electoral bargaining as a determinant for the politicians to win elections. The persistence of poverty in Maranhao and living conditions of the population, demonstrated by the dismal social indicators seem to explain the maintenance of patronage in the state, although this is not restricted only to people who fall into this situation. The population considered to be "literate" contributes to the consolidation of such practices in an attempt to obtain benefits and privileges